2015
DOI: 10.1002/pen.24092
|View full text |Cite
|
Sign up to set email alerts
|

Determination of compounding formulation of cured rubber by reverse engineering

Abstract: The present work deals with reverse engineering on four rubber formulations. Information about the material composition of the compounding formulations was obtained by using techniques such as acetone extract, thermogravimetric analysis, energy dispersive X‐ray fluorescence studies, and Fourier transform infrared (FTIR) spectroscopy in attenuated total reflection mode. The reverse engineered formulations were compared on a qualitative and quantitative basis with the initial formulations. The aim was to ascerta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Truck tires can be made of blends of NR with SBR and BR, which have characteristic bands at 990, 962, 909 and 741 cm −1 . 19,20 According to ASTM D3677, bands from 980 cm −1 to 965 cm −1 are assigned to vibration of C–H link from carbons of butadiene double bond. The characteristic bands of a SBR spectrum are 1490, 962, 909, 758 and 699 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Truck tires can be made of blends of NR with SBR and BR, which have characteristic bands at 990, 962, 909 and 741 cm −1 . 19,20 According to ASTM D3677, bands from 980 cm −1 to 965 cm −1 are assigned to vibration of C–H link from carbons of butadiene double bond. The characteristic bands of a SBR spectrum are 1490, 962, 909, 758 and 699 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the addition of DCSBR with NR decreased tensile elongation at break (E b ), while the hardness was enhanced over the control sample. Sanjoy Datta et al 2 studied the material loss and absorbance bands in the various proportions of developed NR/SBR composites (100/0, 30/70, 50/50, and 70/30) using TGA and Fourier transform infrared (FTIR).…”
Section: Introductionmentioning
confidence: 99%
“…[8] Despite the low reuse and recycling rates, recovered waste tires can be source of valuable raw materials: part of the worn tires is, indeed, still suitable for the on-road applications and it can be, therefore, reused. [9] From the economical point of view, retreading is the most viable way of using ELT since it requires only 30% of energy and 25% of raw materials with respect to the production of a new tire. [10] Several other techniques have been carried out to use ELT, for examples, recycling, [11] reclamation, [12][13][14] devulcanization, [15][16][17] energy recovery, [18,19] and pyrolysis.…”
Section: Introductionmentioning
confidence: 99%